HLA type, islet cell antibodies, and glucose intolerance in cystic fibrosis. Issue 10 (October 1988) - Stutchfield, P R; O'Halloran, S M; Smith, C S; Woodrow, J C; Bottazzo, G F; Heaf, D
Abstract : Impaired glucose tolerance, assessed by a raised glycated haemoglobin (HbA1) concentration, was found in 24 (39%) out of 61 patients with cystic fibrosis with an age range of 1-23 years. No correlation between age and HbA1 concentration was found indicating that factors other than progressive pancreatic fibrosis may be important in the aetiology. HLA typing, islet cell antibodies, and autoantibody screen were completed. Eighteen (75%) out of 24 patients with cystic fibrosis who had an impaired glucose tolerance had HLA-DR3 or HLA-DR4 antigens compared with 23 (62%) out of 37 patients with normal glucose tolerance. Islet cell antibodies were present in seven (15%) out of 46 patients with cystic fibrosis; the prevalence in a normal population is 0.5%. Five (25%) of the 20 patients with a raised HbA1 concentration were positive for islet cell antibodies compared with two (8%) out of the 26 with normal glucose tolerance. Six (86%) out of seven patients who were positive for islet cell antibodies had HLA-DR3 or HLA-DR4 antigens. There was no general autoantibody production. Islet cell antibodies may play a part in the development of glucose intolerance in some patients with cystic fibrosis by being produced in those who are genetically predisposed as part of an immune response to damaged pancreatic tissue.